THE CORRELATION BETWEEN SOCIAL DEIXIS AND SOCIAL CLASS IN A SPEECH BY NOBEL PRIZE WINNERS: A SOCIOPRAGMATIC STUDY - Zulyanputri, Annur Karima; Indrayani, Lia Maulia; Soemantri, Ypsi Soeria (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
This article aims to identify the relationship between one of the linguistic forms such as deixis, specifically social deixis, and the speakers? social class. Thus, the usage of social deixis by Nobel Prize winners in their speech, are analysed. The data are taken from the banquet speech of Nobel Prize winners. This research conducted to find out the types of social deixis used by Nobel Prize winners using Levinson?s theory, which are absolute and relational, and its correlation with speakers? social class. This research applies Block?s theory to provide the aspects or dimensions in social class. Furthermore, other additional theories are also provided to support the main theories. This qualitative descriptive research socio-linguistically provides insight into people?s social class that identified through linguistic feature like social deixis. The findings show that all types of social deixis which are absolute and relational can be identified from every speech uttered by the Nobel Prize winners. In accordance with the social class, only the relational type that can be correlated with the speakers? social class. Through the finding of the research, the relational type of social deixis can determine the speakers? social class dimensions and they are wealth, occupation, education, and social networking.